2006
DOI: 10.5172/ser.14.1.42
|View full text |Cite
|
Sign up to set email alerts
|

SME Innovation within the Australian Wine Industry: A Cluster Analysis

Abstract: This paper assesses core innovation activity among SMEs within different levels of cluster development. The aim of the paper, using empirical data from the Australian wine industry, is to demonstrate that innovation levels and activity intensify as an industry cluster develops. By dividing wine clusters into 'innovative' (highly developed) and 'organised' (less developed) models, the paper uses selected core indicators of innovation activity to explore levels of integration within each model. This integration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 5 publications
2
37
2
2
Order By: Relevance
“…As expected, the Customer is more contributing to entering new markets for the traditional food product' than the food plants manufacturers, thus confirming results from other studies that found that the customers are usually more internationally oriented (Theuvsen, 2004) and that an international market orientation of any member of the chain enhance the innovation capacity of the supply chain as a whole (Aylward and Glynn, 2006;Gellynck et al, 2007). Furthermore, the Customer in the food machinery supply chain is larger sized, result that is perfectly in line with other studies, which stressed that the company size is positively related to the innovation capacity (Avermaete et al, 2003(Avermaete et al, , 2004Coppola and Pascucci, 2008).…”
Section: Conclusion and Recommendationssupporting
confidence: 87%
“…As expected, the Customer is more contributing to entering new markets for the traditional food product' than the food plants manufacturers, thus confirming results from other studies that found that the customers are usually more internationally oriented (Theuvsen, 2004) and that an international market orientation of any member of the chain enhance the innovation capacity of the supply chain as a whole (Aylward and Glynn, 2006;Gellynck et al, 2007). Furthermore, the Customer in the food machinery supply chain is larger sized, result that is perfectly in line with other studies, which stressed that the company size is positively related to the innovation capacity (Avermaete et al, 2003(Avermaete et al, , 2004Coppola and Pascucci, 2008).…”
Section: Conclusion and Recommendationssupporting
confidence: 87%
“…The presence of supporting institutions may positively impact the upgrading of other firms in the local system by not only helping to streamline production and reduce transportation costs, but also enhancing competitiveness through fostering innovation in joint developments. Additionally, the local presence or absence of other industries with activities that are either related or complementary to the cluster's activities can profoundly influence the cluster's competitiveness and innovativeness (Aylward & Glynn, 2006;Miller, So & Williamson, 2011).…”
Section: Porter's Cluster Theory and Firm Innovativenessmentioning
confidence: 99%
“…Australia is too large, so there can be not only one cluster of wine producers, but wine industry as a whole has successfully cooperated with a common strategy for the sole purpose of export-quality wines. Aylward and Glynn (2006) describe the differences in the two types of Australian wine cluster. The South Australian Cluster, which can be described as innovative, and organizational type cluster in Victoria and New South Wales.…”
Section: Methodsmentioning
confidence: 99%